Reflexive Thematic Analysis sebagai Strategi Kualitatif dalam Kajian Pendidikan Multikultural - Nurhaliza, Farah; Putra, Zetra Hainul; Hermita, Neni; Copriady, Jimmy (Innovative: Journal Of Social Science Research, 2025)
This study discusses the reflexive thematic analysis (RTA) approach as an effective qualitative strategy for understandingthe phenomenon of multicultural education. This researchemploys a conceptual paper approach. RTA provides researcherswith the opportunity to actively build themes based on a reflectiveinterpretation of participants' experiences within their socio-cultural contexts. The study focuses on the ethnoparentingpractices of the Malay community in a transmigration area as a case study, illustrating how local cultural values such as religiosity, responsibility, and courtesy are constructed andpassed down in the early childhood education process. Throughin-depth thematic analysis using tools like Nvivo, it was foundthat character education based on local culture plays a significant role in shaping the identity and core values oflearners. RTA proves to be a flexible and profound approach in exploring context-specific educational dynamics, contributingsignificantly to the development of a more inclusive, humanistic, and locally grounded educational model.